Irradiation in a flash: Unique sparing of memory in mice after whole brain irradiation with dose rates above 100 Gy/s. Issue 3 (September 2017) - Montay-Gruel, Pierre; Petersson, Kristoffer; Jaccard, Maud; Boivin, Gaël; Germond, Jean-François; Petit, Benoit; Doenlen, Raphaël; Favaudon, Vincent; Bochud, François; Bailat, Claude; Bourhis, Jean; Vozenin, Marie-Catherine
Abstract: This study shows for the first time that normal brain tissue toxicities after WBI can be reduced with increased dose rate. Spatial memory is preserved after WBI with mean dose rates above 100 Gy/s, whereas 10 Gy WBI at a conventional radiotherapy dose rate (0.1 Gy/s) totally impairs spatial memory.